'A walking Man from the far North' – art, craft and the emergence of consciousness: A speculative tale. Issue 3 (1st December 2015) - Pothier, Benjamin
How can cross-disciplinary speculative narratives give us insights and open new paths of research? Borrowing from a number of disciplines, from Anthropology to Psychology or Art history, I will draw a hypothetical blueprint of processes that possibly led to the creation of the Ainu people's patterns, an indigenous tribe from north Japan. From some particular key points I will narrate a speculative tale giving us possible insights about those specific patterns, as well as about the questions encapsulated in the split representation in the art of Asia and America, questions that were raised by various anthropologists, from Franz Boas to Claude Levi-Strauss. I will demonstrate that those pattern-making habits were inherent to human being as a species until very recently. What kind of unconscious purpose or meaning they could have had and what it could mean in terms of the evolution of consciousness.